Evaluation of various substrates for mycorrhizal inoculum production - PARIHAR, MANOJ; RAKSHIT, AMITAVA; RANA, KIRAN; TIWARI, GOPAL; JATAV, SURENDRA SINGH; RAM, HANUMAN (The Indian Journal of Agricultural Sciences, 2022)
In the present study, six media were standardized to investigate their suitability for on-farm arbuscular mycorrhizal fungi (AMF) production by examining their physical condition and nutrient status which could be a major determinant of AMF propagule in the final product. The experiment was conducted with Sorghum as a host plant which was inoculated with Funneliformis mosseae and Rhizoglomus intraradices. Solirite alone recorded 4.66–24.66% higher root colonization than other medium while for spore density in per g of finished product, solirite and red soil mixture (106.33) was found superior followed by solirite and biochar mixture (94.33) and solirite alone (83), respectively, and lowest in soil medium (63 to 74). Moreover, spore density and root colonization were significantly and positively correlated (R2 = 0.583, P<0.05) with each other. Solirite alone or mixed with other media improved water holding capacity and porosity with optimum nutrient availability which culminated in better host plant growth and ultimately higher number of AMF propagules.